The Effect of Tuition Fees on Student Enrollment and Location Choice: Interregional Migration, Border Effects and Gender Differences - Timo Mitze; Claudia Burgard; Bjoern Alecke (European Regional Science Association (ERSA), 2013)
This paper investigates the effects of tuition fees on the university enrollment and location decision of high school graduates in Germany. After a Federal Constitutional Court decision in 2005, 7 out of 16 German federal states introduced tuition fees for higher education. In the empirical analysis, we use the variation over time and across regions in this institutional change in order to isolate the causal effect of tuition fees on student enrollment and migration. Controlling for a range of regional- and university-specific effects, our results from Difference-in-Differences estimations show that there is generally no effect of tuition fees on internal enrollment rates. However, we find a redirecting effect on first-year students' migratory behavior as indicated by a significant drop in the gross in-migration rates in fee-charging states. Further, our results point at a stronger migration response of male students, which, however, can mainly be attributed to a 'border effect'. That is, interregional migration flows of male students are redirected from fee-charging universities to those universities that are geographically close by while being located in a non-charging neighboring state. Controlling for these border effects, the relocating trend in long-distance migration of university freshmen does not show any particular gender differences.
Keywords: 330; Tuition Fees; Gender Differences; Higher Education; Student Migration; Policy evaluation; Difference-in-Differences